2006
DOI: 10.1634/theoncologist.11-6-681
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Gliomas in Adults

Abstract: Low-grade gliomas are a heterogeneous group of neoplasms usually encountered in younger patient populations. These tumors represent a unique challenge because most patients will survive a decade or more and may be at a higher risk for treatment-related complications. Clinical observations over the years have identified a subset of low-grade gliomas that tends to manifest more aggressive clinical behavior and require earlier, more aggressive intervention. Clinical and molecular parameters may allow better asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 92 publications
0
110
0
12
Order By: Relevance
“…The optimal definition of the entire tumor volume is complicated because gliomas are infiltrating tumors with indistinct borders beyond the radiologic margins. 26,27 However, a previous study has shown that variations between observers caused by imperfect tumor delineation are relatively unimportant, given the large number of data points included in the histogram. 13 Law et al 14 have suggested that the confounding effect of lesion size can be a limitation for the use of SD in predicting the glioma grade.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal definition of the entire tumor volume is complicated because gliomas are infiltrating tumors with indistinct borders beyond the radiologic margins. 26,27 However, a previous study has shown that variations between observers caused by imperfect tumor delineation are relatively unimportant, given the large number of data points included in the histogram. 13 Law et al 14 have suggested that the confounding effect of lesion size can be a limitation for the use of SD in predicting the glioma grade.…”
Section: Discussionmentioning
confidence: 99%
“…However, although our values are consistent with FCM methods reported in the literature (20), the significantly lower pixel-by-pixel PPVs of the automatic method suggest that the proposed segmentation routine is less conservative than the manually defined glioma volumes, consequently including more hyper-intense areas as seen on the T2-w and FLAIR images. Although the metabolically active tumor area is mainly restricted to the visible T2 tumor border (29,30), it is well know that gliomas are infiltrating tumors with indistinct borders on anatomical MR images. This argument should in turn favor a less conservative method for tumor delineation such as the automatic segmentation method, and that a high sensitivity value is more important than a high PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no special care was taken to exclude rCBV pixels from large vessels within the segmented glioma volume. Although large vessels can be appreciated as dark areas on T2-w images and thus should be excluded during the knowledge-based operations (1,3,29), it is well known that the T2*-effect from large vessels in gradient-echo echo-planar perfusion imaging result in an overestimation of the intravascular susceptibility effect in pixels adjacent to large vessels. The consequence of this is overestimated rCBV values in pixels not recognized as vessel tissue by the segmentation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Strategies to improve TMZ effectiveness, such as extended or dose-intense TMZ schedules, the blockade of alkylation DNA repair (ie, using alkyl guanine transferase suicide substrates), or the inhibition of base excision repair, are being evaluated for intracranial gliomas, and may be adapted for the treatment of spinal cord gliomas. [28][29][30] Increasingly, clinical trials of intracranial gliomas stratify patients based on tumor content of the DNA repair enzyme O 6 methylguanine-DNA methyltransferase (MGMT).…”
Section: Discussionmentioning
confidence: 99%